Aesthetic outcomes of non‐functional immediately restored single post‐extraction implants with and without connective tissue graft: A multicentre randomized controlled trial. Issue 6 (24th March 2021) - Ferrantino, Luca; Camurati, Andrea; Gambino, Paolo; Marzolo, Michele; Trisciuoglio, Davide; Santoro, Giacomo; Farina, Vittorio; Fontana, Filippo; Asa'ad, Farah; Simion, Massimo
Abstract: Objectives: To compare the 1‐year aesthetic results of flapless single implants, placed in fresh extraction sockets with bone replacement and immediate provisional restoration with or without a connective tissue graft (CTG). Material and Methods: The present study proposes a partially blinded multicentre parallel randomized controlled trial, where computer‐generated tables were used for central randomization to allocate treatments. A total of 59 of the 60 patients screened by eight private practices in Northern Italy fulfilled the inclusion criteria. Immediate implants were placed in a fresh extraction socket with a non‐functional immediate provisional restoration with (Test group) or without (Control group) a CTG. The primary outcome variable was the implant Crown Aesthetic Index (ICAI) at the 1‐year follow‐up. Results: ICAI for the 59 randomized patients (Test group = 31, Control group = 28) at the 1‐year follow‐up was 4.69 (95% CI = 3.16–6.22) for the Test group and 3.45 (95% CI = 1.83–5.08) for the Control group, without statistically significant difference between the two groups ( p  = .086). One implant failure was recorded in each group, resulting in an implant survival rate of 96.8% [95% CI = 83.3–99.9] for the Test group and 96.4% [95% CI = 81.7–99.9] for the Control group. Other secondary outcome variables and complication rates were comparable across the two groups. Conclusions: Within the limitations of the present clinical trial, the results suggested that the adjunct use of CTG is not mandatory to achieve successful aesthetic outcomes for a well‐planned immediate implant placement with immediate non‐functional provisional restoration in a fresh extraction socket.